Design and fabrication of novel auxetic weft-knitted fabrics with Kevlar yarns. Issue 9 (2nd September 2019) - Xu, Wanli; Sun, Yaxin; Raji, King Rafiu; Ma, Pibo
Abstract: For the purpose of fabricating three kinds of auxetic weft knitted fabrics, three different geometrical structures namely rotational structure, foldable structure and double-headed arrow topological structures with three different knit loop lengths were produced using computerized flat knitting machine. Experimental results show that all three different weft knitted fabrics have auxetic effect. The Poisson's ratio values of the three fabrics are inversely proportional to knit loop lengths. However, differences exist between the curves of Poisson's ratio relative to strain. With regards to the rotational and double-headed arrow topological structures, the curves tend to be monotonic, whilst that of the foldable structure takes the form of a parabola. This research thus confirms the possibility of producing auxetic fabrics based on several geometrical structures using flat knitting technology